EFSUMB Minimum Training Requirements for Rheumatologists Performing Musculoskeletal Ultrasound - Terslev, L.; Hammer, H. B.; Torp-Pedersen, S.; Szkudlarek, M.; Iagnocco, A.; D'Agostino, M. A.; Schmidt, W. A.; Uson, J.; Bruyn, G. A.; Filippucci, E.; Möller, I.; Balint, P.; Wakefield, R.; Naredo, E. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
In order to optimize and standardize musculoskeletal ultrasonography education for rheumatologists, there is a need for competency assessments addressing the required training and practical and theoretical skills. This paper describes how these competency assessments for rheumatologists were developed and what they contain.
Keywords: competency assessment; training; EFSUMB; musculoskeletal ultrasound; rheumatology